2014
DOI: 10.1111/pcn.12153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and diagnostic confirmation of Internet addiction in secondary school students in Wuhan, China

Abstract: Aim: This study investigated the clinical characteristics of internet addiction using a cross-sectional survey and psychiatric interview. Methods:A structured questionnaire consisted of demographics, Symptom Checklist 90, Self-Rating Anxiety Scale, Self-Rating Depression Scale, and Young's Internet Addiction Test (YIAT) was administered to students of two secondary schools in Wuhan, China. Students with a score of 5 or higher on the YIAT were classified as having Internet Addiction Disorder (IAD). Two psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…Regarding psychiatric symptoms, our survey results were not much different from the survey results of other countries. In the previous studies, depressive state, anxiety, insomnia, and ADHD were found to be related to PIU . In our population as well, PIU was associated with such disease symptoms.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Regarding psychiatric symptoms, our survey results were not much different from the survey results of other countries. In the previous studies, depressive state, anxiety, insomnia, and ADHD were found to be related to PIU . In our population as well, PIU was associated with such disease symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…Regarding depressive state, Tang et al . described that along with the deterioration of interpersonal relationships and social function, students with PIU may present loss of self‐confidence and social withdrawal, in association with depression . Regarding anxiety, greater use of the Internet is related to declines in the size of one's social circle, loneliness, lower self‐esteem, and lower life satisfaction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these factors are related to socio-demographic variables such as age (being younger adolescents and younger adults [31,41,42]), gender (being male) [3,11,17,24,25,27,[30][31][32][33][34][41][42][43][44][45][46], female gender [22], higher family income levels [17,44], living in rural areas (for adolescents) [47], living in urban areas (for adults) [34], single parent (for adults) [24,33], marital status (for adults) (being single) [24], income (for adults) (financial difficulties), unemployment (for adults) [11], university year level (being in lower-year levels) (e.g., first or second year) [31,42] and lower school grade levels (for adolescents) [3,22,27], and ethnic group (Asian ethnicity) [38].…”
Section: Risk Factorsmentioning
confidence: 99%
“…It is known that adolescents and young adults are the high-risk groups and more vulnerable for Internet addiction [2]. Both groups especially adolescents suffer from emotional and social stress, in addition to lack of behavioral control due to incomplete psychological maturity, which motivate them to engage in risk-related factors such as Internet addiction [3].…”
Section: Introductionmentioning
confidence: 99%